Technique of blind tracheal intubation in rabbits (Oryctolagus cuniculi) supported by previous maneuver of esophageal cannulization - Falcão,Suyiene Cordeiro (2011)
PURPOSE: To describe and evaluate a modified technique of blind orotraqueal intubation in rabbits, by supporting of previous cannulization of the esophagus. METHODS: Twelve New Zealand rabbits, weighing between 2,780 a 4,140 kg were anesthetized with xilazine (3mg/Kg) and ketamine (20mg/Kg). The animals were positioned in ventral decubitus with the head hyperextend. With one of the hands the anesthetist with the index and thumb fingers positioned in the labial fissures carry on the opening of animal oral cavity. The esophagus was previously cannulized with a tube # 3.5 (3.5mm ID), obstructing its lumen. The trachea lumen was intubated with a probe # 2.5 (2.5mm ID). The positioning of the probe was confirmed through the oscillatory movement of a gauze filament put at outside extremity of tube, resulting from the inspiratory and expiratory flow. RESULTS: The success index was of 100%. CONCLUSIONS: This technique is of easy execution, high success index, sparing the use of several devices for visualization of the larynx and glottis. No complications were observed. It also serves for short period training of human resources.